Penentuan Kadar Logam Berat (As, Ba, Cd, Cr, Hg, Pb, Sb, Se) pada Mainan Anak (Slime, Lapisan Cat, Cat Tangan) dengan Metode SNI ISO 8124-3:2010 Menggunakan ICP-OES - Henny Oktavia; Wilda Eka Cahyani; Budhi Indrawijaya (Program Studi Teknik Kimia, Universitas Pamulang, 2023)
ABSTRACTSafety of children's toys is an important factor that must be considered. Such as the heavy metal content of Arsenic, Barium, Cadmium, Chromium, Mercury, Lead, Antimony and Selenium. Heavy metals are carcinogenic and cause various diseases and poisonings. Heavy metal analysis was carried out using SNI ISO 8124-3 : 2010 method. Sample preparation was carried out by wet destruction which functions to decompose solids from analytes. Variations in the types of toy materials are also needed to see the difference in results. The ICP - OES instrument was chosen because it has a low detection limit, high selectivity, high precision and accuracy, and short measurement time. The instrument system uses plasma as the ionizer and Argon as the carrier gas. From the results of the analysis, the slime contained 0.4343 mg/kg Hg metal (yellow slime), 1.2974 mg/kg Sb metal and 0.5527 mg/kg Pb (red slime). The paint layer contains metal Ba 53.5587 mg/kg (dark green paint layer), metal Pb 1.3923 mg/kg (purple paint layer), metal Hg 0.4546 mg/kg and metal Sb 4.7480 mg/kg (pink paint layer). The hand paint contains As 0.7352 mg/kg (blue hand paint), Ba 61.1159 mg/kg (orange hand paint), 0.7417 mg/kg Hg metal (red hand paint) and 1.0344 Pb metal mg / kg ( purple hand paint ) . The three samples were still declared safe because all metals were still below the maximum limit based on SNI ISO 24-3: 2010.